Using Reading Alouds in Early Childhood Teacher Preparation Programs at University of Cádiz - Trigo-Ibanez, Ester; Rivera-Jurado, Paula; Sánchez-Rodríguez, Susana (Íkala, Revista de Lenguaje y Cultura, 2020)
The objective of this study was to evaluate the effectivenes of a didactic sequence in improving literary reading out loud competence, as reflective formation skill of Early Childhood preservice teachers at University of Cádiz. Within an action-research study, a content analysis of the data collected during the pedagogical sequence was carried out. These data included a list of books selected for reading, video-recordings of the reading-alouds, peer-assessment rubrics, forums for e-self-evaluation launched through the course platform, and a focus group. The results show that the implementation of the sequence was effective in helping students improve their reading aloud competence. In addition, it enabled the compilation of a corpus of works suitable for reading aloud. Nonetheless, some deficiencies were detected in relation to the selection of literary pieces, and some difficulties in the execution of the read-alouds were detected, all of which impeded understanding from the public. In conclusion, the need to integrate linguistic and literary training in the Early Childhood programs is evident and so is the interest in using formative assessment to foster reflective learning.